2013
DOI: 10.1158/0008-5472.can-12-4178
|View full text |Cite
|
Sign up to set email alerts
|

The ShcA PTB Domain Functions as a Biological Sensor of Phosphotyrosine Signaling during Breast Cancer Progression

Abstract: ShcA (SHC1) is an adapter protein that possesses an SH2 and a PTB phosphotyrosine-binding motif. ShcA generally uses its PTB domain to engage activated receptor tyrosine kinases (RTK), but there has not been a definitive determination of the role of this domain in tumorigenesis. To address this question, we employed a ShcA mutant (R175Q) that no longer binds phosphotyrosine residues via its PTB domain. Here, we report that transgenic expression of this mutant delays onset of mammary tumors in the MMTV-PyMT mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 50 publications
3
20
0
Order By: Relevance
“…In transgenic mouse models, deletion of all three ShcA isoforms in the mammary epithelium virtually ablates ErbB2-driven tumor induction (23,25). Using xenograft approaches, an important role for p46/52ShcA during mammary tumor growth, angiogenesis, and metastasis was shown (22,24,25). Our in vivo studies provide the first experimental evidence that p66ShcA contributes to tumor heterogeneity in luminal breast cancers by inducing an EMT.…”
Section: ϫ8mentioning
confidence: 62%
See 2 more Smart Citations
“…In transgenic mouse models, deletion of all three ShcA isoforms in the mammary epithelium virtually ablates ErbB2-driven tumor induction (23,25). Using xenograft approaches, an important role for p46/52ShcA during mammary tumor growth, angiogenesis, and metastasis was shown (22,24,25). Our in vivo studies provide the first experimental evidence that p66ShcA contributes to tumor heterogeneity in luminal breast cancers by inducing an EMT.…”
Section: ϫ8mentioning
confidence: 62%
“…Parental BT474 cells were employed as the negative control. For the small interfering RNA (siRNA) studies, cells were transfected with a pool of three DICER substrate duplex siRNAs targeting mouse Met or with a universal scrambled control (Origene) as described previously (22). Cells were also cultured in the presence of 1 M crizotinib (LC Laboratories) or an equivalent volume of dimethyl sulfoxide (DMSO) for 4 days prior to cell lysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The generation of transgenic mice harboring loss‐of‐function mutations in the PTB domain, SH2 domain, or tyrosine phosphorylation sites of ShcA, which have been inserted into the endogenous locus [Hardy et al, ], have been powerful tools for detailed structure/function analyses of this adaptor. Using these models, we have revealed non‐overlapping roles for each ShcA functional domain during breast cancer progression [Ursini‐Siegel et al, , ; Ahn et al, ]. Individual mutation of the Y239/Y240 or Y313 residues revealed that each phospho‐tyrosine motif relays critical signals that potentiate breast cancer initiation and metastatic progression in MMTV/PyVmT transgenic mice [Ursini‐Siegel et al, ].…”
Section: Adaptor Proteins In Breast Cancer Developmentmentioning
confidence: 99%
“…Mammary tumors expressing one ShcA allele that cannot engage in PTB‐dependent interactions hyper‐activates signaling by establishing an autocrine loop, which activates the fibronectin receptor. Activated Src, in turn, laterally activates multiple RTKs, such as MET, FGFR, and PDGFR, to increase the complexity of tyrosine kinase signaling in breast cancers [Ahn et al, ]. These data suggest that the ShcA PTB domain not only transduces mitogenic stimuli downstream of RTKs but also binds one or more negative regulators, which restrain SH2‐driven ShcA signaling from cytoplasmic pools.…”
Section: Adaptor Proteins In Breast Cancer Developmentmentioning
confidence: 99%